Музыкальная культура личности как элемент профессионального становления будущего специалиста - Акбужурова, С.Ж. (My University, 2013)
This article reviews the process of scientific and methodological support the professional development of students, which will be the specialist of musician education in future. The musical culture of person described as part of the professional becoming process in this article.